Optimal body mass normalization of power output for accurate prediction of estimated cycling performance over complex time-trial courses - Horvath, M.; Andersson, E. P. (Frontiers in Sports and Active Living, 2025)
Introduction: Power profiling is widely used in cycling performance analysis, but both absolute and mass-normalized power outputs have limitations as performance indicators, as they neglect external factors such as terrain, wind, aerodynamic drag, and pacing strategy. To address these limitations, this study introduced a numerical method to quantify how external forces acting on the cyclist influence the conversion of power output into race velocity. Thus, the study aimed to enable accurate prediction of cycling performance based on estimated mean power output over complex time-trial courses.